The relationship between cost system functionality, management accounting practices, and hospital performance - Magdalena Kludacz-Alessandri (Foundations of Management, 2020)
All sophisticated management accounting practices used in hospitals require a functional costing system, which allows for better cost calculation of medical services. This is important for the hospitals because they should always look for the possibilities to improve their outcomes. This study evaluates the effects of various structural factors on quality of costing system and magement accounting practices and examines how these two constructs impact on hospital performance. The data was collected using a questionnaire survey carried out among chief accountants and hospital managers in Polish and English hospitals. Multiple regression was employed to analyze the data. The findings confirmed the earlier studies that hospital performance depends on the quality of cost calculation, as well as on management accounting practices. On the other hand, the quality of cost calculation depends on hospital size and a level of computerization.
Keywords: M41; H83; 650; cost calculation; management accounting; hospital performance; costing system